The Antiatherogenic Potential of Two triterpenes from Protorhus longifolia stem bark (Benrh.) Engl. - Mosa, Rebamang A (University of Pretoria, 2024)
Dissertation (MSc (Biochemistry))--University of Pretoria,2024.